Carbon molecular sieves produced from oil palm shell for air separation - Tan, Soon Tan (Elsevier BV, 2004)
as separation technology by adsorption processes has been widely applied in many related industries, such as petrochemicals, biochemical, environmental technology, oil and gas industries. Oil palm solid waste, the palm shell, was utilized to prepare carbon molecular sieve (CMS) by carbonization for air separation. The effect of different carbonization temperatures on the pore structures and adsorptive properties for oxygen and nitrogen was investigated. CO2 was used as the probing adsorbate at 298 K to characterize the micropore volume and surface area of the CMS. The efficiency in kinetic based separation of air, i.e. selective adsorption of oxygen from nitrogen, was evaluated from the adsorption capacity curves. Results showed that within 1 min of time, one of the samples had shown excellent separation capability, and the O2/N2 selectivity as high as 48 could be obtained. This kinetic selectivity of air was greatly influenced by the carbonization temperatures. The excessive heat at high temperatures has reduced the micropore volume and surface area of the adsorbents, but it has enhanced the oxygen-selective pathway compared with nitrogen. However, the excellent selectivity has affected the overall adsorption capacity to become lower due to the reduction in micropore volume. This study has identified the palm shell as the potential starting material in the preparation of CMS.